LAMANYA KALA II BERDASARKAN PARITAS IBU BERSALIN DI WILAYAH KERJA PUSKESMAS CANGKOLKOTA CIREBON TAHUN 2018 - Ainusyarifah; Ani Nurhaeni; Sumarni (Jurnal Kesehatan Mahardika, 2019)
Maternity mothers who have difficulty adapting to labor pain can cause uncoordinated uterine contractions which result in a disruption in labor and impaired fetal well-being. The purpose of this study was to determine the duration of second stage in primipara, multipara, and grande. The support of the family or the people. Closest to the mother can help ther process oflabor so that it can provide psychological calmness by knowing that someone is accompanying the mother during ther second time to perevent the accurrnce of second time. This reseach uses descriptive type. This study was conducted in the cangkol in 2019. Community Health Center in the City date 01-07 July 2019, The populasion used in this study was 89 respondents, with a sample of 89 respindents . The sampling total sampling, the instrument used is a check sheet. The results of the study showed the duration of the second period based on maternal parity in the primiparous category as 28 respondest (31,46%), the multipara category 43 respondents (46,31%), and the multipara grande category 18 respondents (20,23%). Advice is expected for health workers to increase maternal care during labor in order to prevent the duration of second period.